Detection of wavelength in the range from ultraviolet to near infrared light using two parallel PtSe2/thin Si Schottky junctions. Issue 7 (28th April 2021) - Yang, Wen-Hua; Jiang, Xin-Yuan; Xiao, Yu-Tian; Fu, Can; Wan, Jian-Kun; Yin, Xiang; Tong, Xiao-Wei; Wu, Di; Chen, Li-Miao; Luo, Lin-Bao
Abstract : A new wavelength sensor based on two identical PtSe2 /thin Si Schottky junctions that are able to distinguish wavelength in the range of UV-NIR (265–1050 nm) was proposed. Abstract : A wavelength sensor as a representative optoelectronic device plays an important role in many fields including visible light communication, medical diagnosis, and image recognition. In this study, a wavelength-sensitive detector with a new operation mechanism was reported. The as-proposed wavelength sensor which is composed of two parallel PtSe2 /thin Si Schottky junction photodetectors is capable of distinguishing wavelength in the range from ultraviolet to near infrared (UV-NIR) light (265 to 1050 nm), in that the relationship between the photocurrent ratio of both photodetectors and incident wavelength can be numerically described by a monotonic function. The unique operation mechanism of the thin Si based wavelength sensor was unveiled by theoretical simulation based on Synopsys Sentaurus Technology Computer Aided Design (TCAD). Remarkably, the wavelength sensor has an average absolute error of ±4.05 nm and an average relative error less than ±0.56%, which are much better than previously reported devices. What is more, extensive analysis was performed to reveal how and to what extent the working temperature and incident light intensity, and the thickness of the PtSe2 layer will influence the performance of the wavelength sensor.